Riluzole attenuates acute neural injury and reactive gliosis, hippocampal-dependent cognitive impairments and spontaneous recurrent generalized seizures in a rat model of temporal lobe epilepsy - Kyllo, Thomas; Allocco, Dominic; Hei, Laine Vande; Wulff, Heike; Erickson, Jeffrey D. (Frontiers in Pharmacology, 2024)
Riluzole exhibits neuroprotective and therapeutic effects in several neurological disease models associated with excessive synaptic glutamate (Glu) release. We recently showed riluzole prevents acute excitotoxic hippocampal neural injury at 3 days in the kainic acid (KA) model of temporal lobe epilepsy (TLE). Currently, it is unknown if preventing acute neural injury and the neuroinflammatory response is sufficient to suppress epileptogenesis.The KA rat model of TLE was used to determine if riluzole attenuates acute hippocampal neural injury and reactive gliosis. KA was administered to adult male Sprague-Dawley (250g) rats at 5 mg/kg/hr until status epilepticus (SE) was observed, and riluzole was administered at 10 mg/kg 1 hour and 4 hours after SE and once per day for the next two days. Immunostaining was used to assess neural injury (FJC & NeuN), microglial activation (Iba1 & ED-1/CD68) and astrogliosis (GFAP & vimentin) at day 7 and day 14 after KA-induced SE. Learning and memory tests (Ymaze, Novel object recognition test, Barnes maze), behavioral hyperexcitability tests, and spontaneous generalized recurrent seizure (SRS) activity (24-hour video monitoring) were assessed at 11-15 weeks.Here we show that KA-induced hippocampal neural injury precedes the neuroimmune response and that riluzole attenuates acute neural injury, microglial activation, and astrogliosis at 7 and 14 days. We find that reducing acute hippocampal injury and the associated neuroimmune response following KA-induced SE by riluzole attenuates hippocampal-dependent cognitive impairment, behavioral hyperexcitability, and tonic/clonic generalized SRS activity after 3 months. We also show that riluzole attenuates SE-associated body weight loss during the first week after KAinduced SE.Riluzole acts on multiple targets that are involved to prevent excessive synaptic Glu transmission and excitotoxic neuronal injury. Attenuating KA-induced neural injury and subsequent microglia/astrocyte activation in the hippocampus and extralimbic regions with riluzole reduces TLE-associated cognitive deficits and generalized SRS and suggests that riluzole could be a potential antiepileptogenic drug.